PENYULUHAN KESEHATAN: IDENTIFIKASI RESIKO DIABETES MELITUS PADA REMAJA DI SMA 8 KOTA MATARAM NUSA TENGGARA BARAT TAHUN 2022 - Heny Marlina Riskawaty (Jurnal LENTERA, 2022)
Diabetes mellitus ( dm ) is disease characterized by the hiperglikemia and impaired metabolism of carbohydrates , fat , and protein linked by deprivation in absolute terms or relatively from work and or secretion of insulin .Is a symptom of diabetes mellitus is polidipsia , polyuria , polifagia , weight loss , and not only is diabetes mellitus at adult age , but also occurs with early adolescence .The purpose is to identifys: knowledge teenagers about diabetes mellitus .The time it takes the implementation is up to 1 week .The teenagers were respondents participate in finish this up , and bmi (body mass index) teidentifikasi normal and good knowledge teenagers .Can be expected in the local community health partnership with senior high school to more intensive counseling about preventing diabetes mellitus in adolescents .